A Comparative Analysis of the Implementation of Regional Head Elections in Mojokerto Regency and Kuantan Singingi Regency - Kencana Asmanto; Ataya Qonita Ananta; Virani Nabillah Putri; Iradhad Sihidi; Ach. Romadhan (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2026)
This study examines the implementation of the Regional Head Election (Pilkada) in Mojokerto Regency, East Java, and Kuantan Singingi Regency, Riau. This study uses a comparative method with a descriptive qualitative approach. The focus of the study includes the level of public participation, the quality of the election implementation, and the effectiveness of the election implementation. The results of the analysis show significant differences, especially in terms of political participation patterns where Mojokerto Regency shows a very consistent increasing trend from 60% (2015) to 86.67% (2024), an increase of 26.67 percentage points and exceeding the national average. Meanwhile, Kuantan Singingi Regency experiences fluctuations with a